Web Pages Categorization Based on Classification & Outlier Analysis through FSVM - R.B, Geeta; R.B, Shobha; Totad, Shashikumar G; PVGD, Prasad Reddy (Review of Computer Engineering Research, 2014)
The performance of Support Vector Machine is higher than traditional algorithms. The training process of SVM is sensitive to the outliers in the training set. Here in this Paper, a new approach called, Web Pages Categorization based on Classification and Outlier Analysis (WPC-COA), is proposed that uses a polynomial Kernel function to map web page tuples to high dimensional feature space.